2021
DOI: 10.1063/5.0040803
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of virus transmission through droplets from sneezing in a cafeteria

Abstract: To provide a comprehensive understanding of virus transmission inside small indoor spaces, numerical simulation of sneezing droplets spreading in a cafeteria is conducted through computational fluid dynamics. The numerical results show that dining face to face is extremely vulnerable to direct infection by others' respiratory droplets. Different heights of droplet sources are compared, which indicates that sneezing from a standing person results in a longer survival time of droplets in the air. Scenarios with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Even with those protective measures, it is difficult to establish specific safety guidelines for diverse environmental conditions and various situations. 18 Thus, it is necessary to understand the aerodynamic movement of droplets in specific situations, implementing different scenarios with various mask performance and ambient air flow conditions. There have been efforts to investigate droplet propagation by simulating human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Even with those protective measures, it is difficult to establish specific safety guidelines for diverse environmental conditions and various situations. 18 Thus, it is necessary to understand the aerodynamic movement of droplets in specific situations, implementing different scenarios with various mask performance and ambient air flow conditions. There have been efforts to investigate droplet propagation by simulating human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Amid the outbreak of COVID-19, the focus has now shifted to the investigation of the transmission of SARS coronavirus-2 viruses in the form of aerosols and droplets in public places and to the respiratory tract. A plethora of research has been conducted in recent times to study the transmission behavior of SARS coronavirus-2 in various public places, such as elevators ( Dbouk and Drikakis, 2021 ), escalators ( Li et al , 2021a ), dental clinics ( Li et al , 2021b ), hospital isolation rooms ( Bhattacharyya et al , 2020 ), vehicle parking areas ( Nazari et al , 2021 ), buses ( Zhang et al , 2021 ), passenger aircraft ( Talaat et al , 2021 ), classrooms ( Foster and Kinzel, 2021 ), restaurants and cafeterias ( Liu et al , 2021 , Wu et al , 2021 ), conference rooms ( Mirikar et al , 2021 ), classrooms ( He et al , 2021 ), public restrooms ( Schreck et al , 2021 ), in a city ( Zheng et al , 2021 ), and even during a face-to-face scenario with an utterance ( Ishii et al , 2021 ). On the other hand, Jarvis (2020) found that the SARS coronavirus-2 borne aerosol particles can combine with particulate matter (PM) present in the atmosphere, possibly leading to even higher infection rates.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these methods, sometimes people can find themselves in a relatively closed space, such as taking public transportation, 9 dining in a restaurant, 10 and hospitals. 11 In these cases, SARS-CoV-2 can be spread in an enclosed space if an infected person spends time in this place.…”
Section: Introductionmentioning
confidence: 99%